Clinical features of multiple cutaneous and uterine leiomyomatosis: an underdiagnosed tumor syndrome. - Alam, N; Barclay, E; Rowan, A; Tyrer, J; Calonje, E; Manek, S; Kelsell, D; Leigh, I; Olpin, S; Tomlinson, I (2005)
OBJECTIVE: To investigate the clinical features of the multiple cutaneous and uterine leiomyomatosis (MCUL) syndrome, including the hereditary leiomyomatosis and renal cell cancer syndrome. DESIGN: A case series of patients with multiple skin leiomyomas solicited via a circular letter to dermatologists. SETTING: Research institute. PATIENTS: A total of 108 affected individuals, including 46 probands and 62 affected relatives. MAIN OUTCOME MEASURES: The proportion of probands with underlying fumarate hydratase (FH) mutations, the penetrance of FH mutations, and clinicopathologic features of MCUL. RESULTS: Forty-one (89%) of 46 probands with multiple skin leiomyomas had evidence of germline FH mutations, which were highly penetrant. All 26 male mutation carriers had skin leiomyomas. Of 67 women with FH mutations, 46 (69%) had both skin and uterine leiomyomas; 10 (15%) had only skin leiomyomas; 5 (7%) had only uterine leiomyomas; and 6 (9%) were clinically unaffected. Patients presented with skin leiomyomas at a mean age of 24 years and had a mean of 25 lesions. Forty-one individuals (89%) reported painful lesions, particularly in response to cold or trauma. Fibroids were histologically unremarkable, highly symptomatic, and associated with a high risk of early hysterectomy. One individual had a very aggressive collecting duct renal cancer. The G354R FH mutation predisposed patients to uterine fibroids without skin leiomyomas (P = .03). Many patients with skin leiomyomas had not previously presented for medical attention. Fibroids were rarely recognized as cases of MCUL. CONCLUSIONS: Highly penetrant FH mutations underlie MCUL. Increased clinical awareness is important because of the associated risk of severe uterine fibroids and, in some cases, aggressive renal cancer.